'Breaks of gauge' in Australian railway history: the significance of standardisation in national infrastructures. (26th December 2019) - Lee, Heejin; Liebenau, Jonathan; Fomin, Vladislav V.
Australia's railway suffered from breaks of gauge from the beginning of the systems' development in the 1850s and long after the foundation of the federation in 1901. The failure was caused by economic, social and political factors, and it brought significant consequences for each of those domains. While explaining the causes and impacts of breaks of gauge, we consider economic and technological factors in the development of the railway network. We suggest that economic considerations of Australian territories and the governance structure of the federation were the key factors causing the breaks of gauges. The consequences were significant for economic development and demonstrate the prominence of standardisation in the technological and economic development of national infrastructures. The lessons learned have implications for standardisation in developing national infrastructures.